A resolution at midnight - Noble, Shelley (Noble, Shelley. Lady Dunbridge mystery., 2020)
"It's Christmas in Gilded Age Manhattan. And for the first time ever an amazing giant ball will drop along a rod on the roof of the New York Times building to ring in the New Year. Everyone plans to attend the event. But the murder of a prominent newsman hits a little too close to home. And when a young newspaper woman, a protégé of the great Jacob Riis and old Vassar school chum of Bev's, is the target of a similar attack, it is clear this is not just a single act of violence but a conspiracy of malicious proportions."--